2013
DOI: 10.1080/19942060.2013.11015486
|View full text |Cite
|
Sign up to set email alerts
|

Micro Scale Heat Transfer Comparison between Packed Beds and Microfibrous Entrapped Catalysts

Abstract: Computational Fluid Dynamics (CFD) was used to compare the micro scale heat transfer inside a packed bed and a microfibrous entrapped catalyst (MFEC) structure. Simulations conducted in stagnant gas determined the thermal resistance of the gas in the micro gaps between the particle-to-particle contact points in the resistance network model of a packed bed. Tube to particle diameter ratios for the simulations were 9 based on particle diameter and 27 for MFEC based on surface area average diameter. The maximum t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…For the MFECC bed, the maximum temperature at the centerline of the reactor remains almost constant under all GHSV conditions (5000 h −1 to 10,000 h −1 ) at 534.5 K. Therefore, operating at higher velocities induces very small changes in the thermal behavior of the MFECC bed. The observations in the thermal behavior of both the PBR and MFECC discussed above are also supported by a modeling study conducted by Sheng et al, who conducted a microscale heat transfer comparison between a PBR and an MFECC bed in a stagnant gas and flowing nitrogen gas conditions [62]. They reported that 97.2% of the total heat flux transferred within the MFECC bed was found to be transported by the continuous metal fibers.…”
Section: Effect Of Varying the Ghsvsupporting
confidence: 64%
“…For the MFECC bed, the maximum temperature at the centerline of the reactor remains almost constant under all GHSV conditions (5000 h −1 to 10,000 h −1 ) at 534.5 K. Therefore, operating at higher velocities induces very small changes in the thermal behavior of the MFECC bed. The observations in the thermal behavior of both the PBR and MFECC discussed above are also supported by a modeling study conducted by Sheng et al, who conducted a microscale heat transfer comparison between a PBR and an MFECC bed in a stagnant gas and flowing nitrogen gas conditions [62]. They reported that 97.2% of the total heat flux transferred within the MFECC bed was found to be transported by the continuous metal fibers.…”
Section: Effect Of Varying the Ghsvsupporting
confidence: 64%
“…The radial temperature distribution was mostly uniform along the radial direction, with a large temperature gradient near the reactor wall (Figure ). Compared with that of the packed-bed reactor, the temperature difference between the centerline and the near-wall region was at least 100 times smaller for the MFEC reactor than the packed-bed reactor running at even lower face velocity . The majority of catalyst particles remained in a small temperature range for the MFEC reactor because of the uniform temperature distribution, whereas only a small portion of the catalyst was at the desired temperature for the packed bed .…”
Section: Resultsmentioning
confidence: 95%
“…The temperature distribution profile for any reactive structure that operates at high velocity can be calculated by numerically solving the equation with adjusted axial and radial thermal conductivities. Sheng et al experimentally and theoretically studied the temperature distribution in packed beds during highly exothermic reactions . The radial temperature distribution was found to exhibit a large gradient between the centerline and the near-wall region because of the poor effective thermal conductivity of packed beds.…”
Section: Resultsmentioning
confidence: 99%
“…This was also concluded by Zhu et al (2007Zhu et al ( , 2008) during a review on particulate flows modelled with the CCDM approach. Based on this approach Sheng et al (2013) investigated into the micro-scale heat transfer of packed beds and micro-fibrous entrapped catalysts and concluded that the thermal resistance of the contact points account for more than 90 % of the total resistance. Similarly, Kon et al (2013) modelled the liquid flow in the lower part of a blast furnace by the MPS method.…”
Section: Introductionmentioning
confidence: 99%
“…CCDM has seen a mayor development in last two decades and describes motion of the solid phase by the Discrete Element Method (DEM) on an individual particle scale and the remaining phases are treated by the Navier-Stokes equations. However, current CCDM approaches should be extended to a truly multi-phase flow behaviour as opposed to the Volume-of-Fluid method and the multi-phase mixture model stated by Sheng (2013). Furthermore, particle shapes other than spherical geometries have to be taken into account to meet engineering needs according to Zhu et al (2007Zhu et al ( , 2008.…”
Section: Introductionmentioning
confidence: 99%